2014
DOI: 10.1186/1478-7954-12-18
|View full text |Cite
|
Sign up to set email alerts
|

The diabetes-obesity-hypertension nexus in Qatar: evidence from the World Health Survey

Abstract: BackgroundAs countries develop economically, an “epidemiological transition” occurs whereby a set of chronic diseases increasingly becomes a country’s health challenge. Against this background, this paper examines the most common conditions associated with the prevalence of diabetes in Qatar, with a specific focus on the diabetes-obesity-hypertension nexus.MethodsWe analyzed data from the World Health Organization’s World Health Survey conducted in the State of Qatar in 2006. The survey included demographic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 20 publications
(19 reference statements)
2
32
0
Order By: Relevance
“…However, many of them bring their families and parents to KSA, and their relatives receive medical care in the Kingdom. In addition, previous studies have shown that immigrants tend to pick up the host country's health habits through acculturation [24][25][26][27]. Finally, we did not account for the potential cost of undiagnosed diabetes among those under the age of 15 in our projections since SHIS did not include them, although we have included their current cost from MOH data.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of them bring their families and parents to KSA, and their relatives receive medical care in the Kingdom. In addition, previous studies have shown that immigrants tend to pick up the host country's health habits through acculturation [24][25][26][27]. Finally, we did not account for the potential cost of undiagnosed diabetes among those under the age of 15 in our projections since SHIS did not include them, although we have included their current cost from MOH data.…”
Section: Discussionmentioning
confidence: 99%
“…When non-nationals are excluded, the prevalence of diabetes is even higher (Ali et al, 2014;Hajat et al, 2012;Malik et al, 2005). For example, one study found an age-adjusted diabetes prevalence of 25 percent among UAE nationals, whereas the prevalence among non-national groups ranged from 16 to 21 percent, depending on the country of origin (Malik et al, 2005).…”
Section: 1mentioning
confidence: 99%
“…RAND RR889-3.3 Prevalence (%) higher than the OECD average of 22 percent, and that are close to or exceed that of the United States, which has the highest rate in the OECD, at 33 percent. In GCC countries, obesity rates are higher for nationals than non-nationals; in Qatar, for example, a study showed that 42 percent of nationals and 29 percent of non-nationals were obese (Ali et al, 2014). Especially alarming is the high prevalence of obesity in younger age cohorts.…”
Section: Metabolic Risk Factors Lead To High Chronic Disease Ratesmentioning
confidence: 99%
“…These rapid changes have largely influenced the country's traditional dietary choices and nomadic lifestyle. Today, Qatar's population has some of the highest rates of obesity and diabetes in the world (Ali et al 2014). Fears of obesity and cultural stereotyping of obese individuals are on the rise especially among women in this part of the world (Musaiger 2015).…”
Section: Introductionmentioning
confidence: 99%